2018
DOI: 10.1001/jamaoto.2018.0272
|View full text |Cite
|
Sign up to set email alerts
|

Association of Behavior With Noise-Induced Hearing Loss Among Attendees of an Outdoor Music Festival

Abstract: IMPORTANCETo date, factors associated with noise-induced hearing loss at music festivals have not yet been analyzed in a single comprehensive data set. In addition, little is known about the hearing loss-associated behavior of music festival attendees.OBJECTIVES To assess which factors are associated with the occurrence of a temporary threshold shift (TTS) after music exposure and to investigate the behavior of music festival attendees. MAIN OUTCOMES AND MEASURESThe primary outcome was a TTS on a standard aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…The rationale behind this is that results of the previously conducted survey revealed that event visitors are already convinced that ringing in the ears and hearing damage are undesirable, but that a good fit and pricequality trade off regarding ear plugs is very important (and conversely, a lack of each potentially prohibitive). This is in line with previous research indicating high awareness of the benefits of using ear plugs (Beach, Williams, and Gilliver 2012), but at the same time loudness and appreciation of music being associated with the intention to use them (Kraaijenga, Van Munster, and Van Zanten 2018). Cheaper foam ear plugs are considered less satisfactory than more expensive ear plugs, which are relatively discreet and comfortable, facilitate communication with others, create minimal music distortion and, in some cases, improve music sound quality (Beach, Williams, and Gilliver 2010).…”
Section: Intervention Activitiessupporting
confidence: 89%
See 1 more Smart Citation
“…The rationale behind this is that results of the previously conducted survey revealed that event visitors are already convinced that ringing in the ears and hearing damage are undesirable, but that a good fit and pricequality trade off regarding ear plugs is very important (and conversely, a lack of each potentially prohibitive). This is in line with previous research indicating high awareness of the benefits of using ear plugs (Beach, Williams, and Gilliver 2012), but at the same time loudness and appreciation of music being associated with the intention to use them (Kraaijenga, Van Munster, and Van Zanten 2018). Cheaper foam ear plugs are considered less satisfactory than more expensive ear plugs, which are relatively discreet and comfortable, facilitate communication with others, create minimal music distortion and, in some cases, improve music sound quality (Beach, Williams, and Gilliver 2010).…”
Section: Intervention Activitiessupporting
confidence: 89%
“…Although younger adults were a bit more likely to use them, there is still much room for improvement (Eichwald et al 2018). Furthermore, not using ear plugs in combination with using alcohol and/or drugs might be positively associated with developing temporary noise-induced hearing loss at music events (Kraaijenga, Van Munster, and Van Zanten 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind this is that results of the previously conducted survey revealed that event visitors are already convinced that ringing in the ears and hearing damage are undesirable, but that a good fit and price-quality trade off concerning ear plugs is very important (and conversely, a lack of each potentially prohibitive). This is in line with previous research indicating high awareness of the benefits of using ear plugs (Beach, Williams, & Gilliver, 2012), but at the same time loudness and appreciation of music being associated with the intention to use them (Kraaijenga et al, 2018). Cheaper foam ear plugs are considered less satisfactory than more expensive ear plugs, which are relatively discreet and comfortable, facilitate communication with others, create minimal music distortion and, in some cases, improve music sound quality (Beach, Williams, & Gilliver, 2010).…”
Section: Intervention Activitiessupporting
confidence: 92%
“…Furthermore, not using ear plugs in combination with using alcohol and/or drugs might be positively associated with developing temporary noise-induced hearing loss at music events (Kraaijenga, Van Munster, & Van Zanten, 2018).…”
mentioning
confidence: 99%
“…Further, there was a non-statistically significant trend for men who reported any DPM to have poorer mid-frequency DPOAEs compared to No DPM men. The research literature generally supports an association between level of environmental music and alcohol consumption [20,22,23] and results of a recent field study showed an association between alcohol and/or drug use and temporary noise-induced hearing loss among attendees of an outdoor music festival in the Netherlands [41]. However, more investigation is needed in the field to collect data on noise levels in settings where alcohol is consumed while measuring the alcohol consumed in those settings.…”
Section: Discussionmentioning
confidence: 87%